2022
DOI: 10.1002/ccd.30317
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous closure of patent foramen ovale for treatment of hypoxemia: A case series and physiology review

Abstract: Intracardiac right-to-left shunt (RTLS) mediated hypoxemia is a rare complication of patent foramen ovale (PFO). The process may be potentiated by reversal of the usual trans-atrial pressure gradient, or from alteration of intracardiac geometry such that venous flow is preferentially directed toward the PFO. We describe a series of four patients who presented with hypoxemia, detailing the diagnostic evaluation which led to the ascertainment of intracardiac RTLS across PFO as the culprit pathology. All underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This finding provides real-world evidence to support the relationship between PFOs and migraine. One of the main hypotheses is that PFO-induced RLS caused venous blood to mix with arterial blood, resulting in lower blood oxygen content being delivered to the brain [9,10], and therefore hypoxemia in the brain [13]. Surprisingly, several clinical investigations have shown that hypoxia may cause migraines and auras [14].…”
Section: Nbo May Inhibit Pfo-migrainementioning
confidence: 99%
See 1 more Smart Citation
“…This finding provides real-world evidence to support the relationship between PFOs and migraine. One of the main hypotheses is that PFO-induced RLS caused venous blood to mix with arterial blood, resulting in lower blood oxygen content being delivered to the brain [9,10], and therefore hypoxemia in the brain [13]. Surprisingly, several clinical investigations have shown that hypoxia may cause migraines and auras [14].…”
Section: Nbo May Inhibit Pfo-migrainementioning
confidence: 99%
“…The widely accepted theory is that brain function is influenced by oxygen supply, as glucose and oxygen are the two most important substrates for oxidative metabolism in the brain. Under hypoxic conditions, mitochondria are unable to produce enough ATP to maintain activity of ion pumps in the brain [13]. This results in a series of changes to transmembrane electrochemical gradients, such as rapid and widespread membrane depolarization, which may lead to widespread depression of synaptic transmission and slowing of electric activity [2] (Fig.…”
Section: Nbo May Abrogate Abnormality Of Brain Activitymentioning
confidence: 99%